Uso dos softwares construfig3d, poly, geogebra e sketchup nas aulas de geometria espacial - Maia, Marcelo Batista Pascoal (2015)
The present study aims to show possibilities concerning to spatial geometry through the creation and viewing of spatial figures and their elements in the softwares like construfig3D, poly, geogebra e sketchp. After a brief presentation of the use of softwares in spatial geometry classes, I introduce the tools used in the softwares e their possibilities. Both are able to look at the figures in three dimensions. In the end, I present several situations involving the use of the softwares and the following concepts: polyhedra, Euller´s method, height of pyramids, parallelepiped´s diagonal, flat sections of a cube, cylinders, cones, balls, circumscription and inscription of spatial figures, unfoldments and solving problems.